2021
DOI: 10.1177/14707853211007785
|View full text |Cite
|
Sign up to set email alerts
|

Low-literate versus literate customer experience: Dimensions, consequences and moderators

Abstract: This study explores the lived phenomenon of customer experience (CX) across the customer decision journey of two divergent segments of customers in a naturalistic environment. Specifically, the study focusses on understanding the similarities and differences with respect to—(a) dimensions of CX, (b) consequences of CX, (c) moderators of CX, and (d) situating CX in customer decision journey. The findings are in congruence with the various theories from cognitive psychology, environmental psychology, and economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…Finally, as expected, satisfaction influences patronage. As called for by past studies (e.g., Blut et al, 2018;Mishra and Verma, 2022), we consolidate the prior findings by confirming the presence and absence of these interdependencies amongst these retailerrelevant constructs. Thus, our framework provides academic conclusions about the previously understudied population of LLCs so that retailers can gain deeper insights to serve them.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Finally, as expected, satisfaction influences patronage. As called for by past studies (e.g., Blut et al, 2018;Mishra and Verma, 2022), we consolidate the prior findings by confirming the presence and absence of these interdependencies amongst these retailerrelevant constructs. Thus, our framework provides academic conclusions about the previously understudied population of LLCs so that retailers can gain deeper insights to serve them.…”
Section: Discussionsupporting
confidence: 87%
“…Literacy is defined as "using printed and written information to function in society, to achieve one's goals, and to develop one's knowledge and potential" (Kirsch et al, 1993). Given such obscurity, we follow the conceptualization of Jae et al (2011, p. 312) and consider customers "who can read but not as well as the average adult" to be low literate (see also Mishra and Verma, 2022).…”
Section: Conceptual Background Low-literate Customersmentioning
confidence: 99%
See 2 more Smart Citations
“…De Keyser et al (2020) suggested in their study that improving customer experience through touchpoints depends in part on income. Mishra and Verma (2022) attempted to comprehend the role of client qualities, such as income level, in defining the customer experience in a different piece of work. Moreover, Manyanga et al (2022) examined the impact of customer demographics as moderators in their experience formation.…”
Section: Hypotheses Formationmentioning
confidence: 99%